Sparing internal thoracic vessels in thoracoscopic or submuscular correction of pectus carinatum: a porcine model study - Pinheiro, Ruben Lamas (2016)
Supplementary data to this article can be found online at http://dx. doi.org/10.1016/j.jpedsurg.2015.07.023.